1998
DOI: 10.1111/j.1754-4505.1998.tb01139.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and treatment needs of Canadian adults aged 85 years and over

Abstract: In an oral health survey, 1375 adults aged 85 and older were examined in North York, Canada. Only 31% of dentate nursing home residents and 47% of dentate independently living subjects had received dental care in the year previous to examination. The overall prevalence of edentulism was 66%, and about 80% of subjects wore at least one denture. Of the dentate subjects, over 60% had untreated decay, and 47% of nursing home residents had untreated root decay. Regarding clinically defined treatment needs, high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 13 publications
2
38
3
Order By: Relevance
“…Four other Canadian studies on oral health status of long‐term care residents have studied participants from a single province or community using cross‐sectional data gathered through oral examinations by either a dentist or dental hygienist: Nova Scotia (n = 335); North York, Ontario (n = 1375 over a data collection period of 10 years); Edmonton, Alberta (n = 63); and Vancouver, British Columbia (n = 369) . The average number of teeth found in this study (16.4) is consistent with that found by Wyatt (16.4) and Kuc (17.1) but more than that found by Hawkins (11.9), who only included older adults aged 85 and older. Nearly twice the number of residents in this study wore complete dentures compared to those found by Wyatt (25%), whose study purpose was to recruit individuals for a mouth rinse clinical trial, possibly increasing the proportion of participants with dentition.…”
Section: Discussionmentioning
confidence: 99%
“…Four other Canadian studies on oral health status of long‐term care residents have studied participants from a single province or community using cross‐sectional data gathered through oral examinations by either a dentist or dental hygienist: Nova Scotia (n = 335); North York, Ontario (n = 1375 over a data collection period of 10 years); Edmonton, Alberta (n = 63); and Vancouver, British Columbia (n = 369) . The average number of teeth found in this study (16.4) is consistent with that found by Wyatt (16.4) and Kuc (17.1) but more than that found by Hawkins (11.9), who only included older adults aged 85 and older. Nearly twice the number of residents in this study wore complete dentures compared to those found by Wyatt (25%), whose study purpose was to recruit individuals for a mouth rinse clinical trial, possibly increasing the proportion of participants with dentition.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the oral health status of at risk children and adolescents appears to be poor resulting in the need for several treatments including urgent, restorative, periodontal and preventive care [4-6]. Similarly, very high levels of unmet need among older adults have been observed regardless of whether they live in an institution or are homebound [7]. The treatments they require have been reported as consisting of urgent, preventive, periodontal, restorative and prosthodontic care [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, very high levels of unmet need among older adults have been observed regardless of whether they live in an institution or are homebound [7]. The treatments they require have been reported as consisting of urgent, preventive, periodontal, restorative and prosthodontic care [7]. Other studies of need have also relied on self-reported information.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous generations, more and more older adults are maintaining their natural teeth into old age [1–3]. This is a welcome trend but results in new patterns of disease that become especially significant for those who are frail and who must depend on others for their personal care and hygiene [4–6].…”
Section: Introductionmentioning
confidence: 99%